Nursing Mental Health Issues: Prospective Pathways Forward from a Comprehensive Review of Impacts Before and Throughout COVID-19 - Çerçizaj Rudina; Kamberi Fatjona; Kiçaj Emirjona; Prifti Vasilika; Qirko Sonila; ROGOZEA Liliana (RREM (Revista Românească pentru Educaţie Multidimensională) Publisher: In Manifest Network (in partnership with LUMEN Publishing), 2025)
Nurses face significant challenges, including long shifts and heavy workloads, which can negatively impact their mental health, contributing to depression, anxiety, burnout, and fatigue. These factors make nurses more vulnerable to mental health difficulties compared to the general population. We conducted a systematic review to assess the mental health effects of nursing work before and throughout the COVID-19 pandemic, the contributing factors, and potential solutions. Our search of Pub Med, Medline, Scopus, Elsevier, Frontiers, and Psych Info databases included studies from 2004 to 2023, resulting in 35 studies: 22 focused on COVID-19, two on SARS, one on MERS-COV, one on nurses' mental health before and throughout the pandemic, and 10 on non-epidemic periods. Common mental health symptoms found in the analysis included anxiety, stress, PTSD, depression, burnout, and sleep difficulties. Risk factors included caring for patients with COVID-19, working in high-risk departments, heavy workloads, lack of resources, long shifts, and being female. Additional factors, such as inadequate training, societal support, and marital status, also played a role. During the COVID-19 pandemic, nurses faced heightened mental health issues compared to prior periods. Proper psychological support is essential to equipping nurses for the challenges ahead. This article emphasises the need for enhanced mental health strategies targeted at nurses in emergency and everyday healthcare settings, offering recommendations for policymakersto create more supportive work environmentS.
Keywords: nurse; mental health; COVID-19; systematic review; before-after pandemic.